Personal, socio-economic and psychological characteristics of coconut growers - K, Mohith; Narayanaswamy, C (International Journal of Environment, Agriculture and Biotechnology, 2024)
The present study to know the personal, socio-economic and psychological characteristics of randomly selected 120 coconut growers from Tiptur, Turuvekere, Chikkanayakanahalli and Sira taluks of Tumkur district was conducted during the year 2022-23. Overall it was found that equal number of coconut growers (42.50 %) were in the old and middle age group respectively, while significant number of coconut growers (37.50 %) were having education upto high school, two-third of coconut growers (69.16 %) were found under the category of medium family size, while two-fifth of coconut growers (40.00 %) came under big farmers category followed by 39.16 per cent under the small farmers category and more than two-fifth of coconut growers (46.66 %) possessed medium level of farming experience. Overall it was found that significant number of coconut growers (44.20 %) belonged to medium category of information seeking behaviour, more than two-fifth of coconut growers (43.33 %) came under medium category of extension participation, two-fifth of coconut growers (40.00 %) belonged to medium category of management orientation. Among the overall coconut growers, it was disclosed that significant number of coconut growers i.e., 46.67 per cent were found equally under the medium category of risk orientation, credit orientation, innovativeness. Overall it was found that slightly more than two-fifth of coconut growers (41.67 %) were having medium level of deferred gratification, significant number of coconut growers (46.67 %) belonged to medium category of scientific orientation and significant number of coconut growers (44.17 %) belonged to medium category of cosmopoliteness.